Essays on unemployment, marginal attachment and married women in the labor market - Adorna, Luzeta C. (Ann Arbor, MI ProQuest Dissertations & Theses Global, 2007)
The research examines the labor market behavior of individuals at the margin of the labor force and that of married women. The first study asks whether discouraged workers and other individuals at the margin should be classified with the unemployed. The second tests whether married women increase their number of hours of work in response to their husbands' unemployment, while a related third paper investigates whether the receipt of unemployment insurance dampens that response. The data used are the short panels of the Current Population Survey and the Survey of Income and Program Participation for the years 1996-2004, permitting analyses of labor market behavior through cyclical changes in labor demand. Using parametric discrete choice models, the results from the first investigation support the current classification: the unemployed and the marginally attached are highly distinct groups even during the last recession and a separate classification is justified. Nevertheless, the findings suggest that about half of the marginally attached have strong ties to the labor market, and even higher proportion for passive job searchers. Labor market attachment indicators can provide a business cycle sensitive adjustment for the BLS's alternative measures of labor underutilization.
Thesis (PhD)--Syracuse University, 2007.
Includes bibliographical references (pages 106-108)
Keywords: Electronic books; Women's studies; Labor economics; Sociology; Industrial relations